(untitled) (The Pakistan Development Review, 2000)
Income, Money, and Prices are important macroeconomic variables which play crucial roles in an economy. There has been a long debate in economics regarding their roles. For example, the Monetarists claim that money plays an active role and leads to changes in income and prices. In other words, changes in income and prices in an economy are mainly caused by the changes in money stocks. The Keynesians, on the other hand, argue that money does not play an active role in changing income and prices. In fact, changes in income cause changes in money stocks via demand for money. Similarly, changes in prices are mainly caused by structural factors.